2019
DOI: 10.1161/strokeaha.119.025085
|View full text |Cite
|
Sign up to set email alerts
|

Role of TLR4 (Toll-Like Receptor 4) in N1/N2 Neutrophil Programming After Stroke

Abstract: Background and Purpose— After stroke, the population of infiltrated neutrophils in the brain is heterogeneous, including a population of alternative neutrophils (N2) that express M2 phenotype markers. We explored the role of TLR4 (toll-like receptor 4) on neutrophil infiltration and polarization in this setting. Methods— Focal cerebral ischemia was induced by occlusion of the middle cerebral artery occlusion in TLR4-KO and WT (wild type) mice. Infarct s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
113
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(115 citation statements)
references
References 27 publications
1
113
0
1
Order By: Relevance
“…Then, dual-luciferase reporter assay was employed and veri ed that miR-140-5p bound to TLR4. Most interestingly, TLR4 has been suggested to play the crucial role of in stroke, which could mediate several pathways related to in ammation or migration of neutrophils into the parenchyma that induced by ischemia [41]. Hence, we guessed that TLR4 may be involved in the ischemic stroke affected by miR-140-5p, which was validated by means of RT-qPCR, Western blot, ow cytometry, and TTC staining, as well as TUNEL staining.…”
Section: Discussionmentioning
confidence: 78%
“…Then, dual-luciferase reporter assay was employed and veri ed that miR-140-5p bound to TLR4. Most interestingly, TLR4 has been suggested to play the crucial role of in stroke, which could mediate several pathways related to in ammation or migration of neutrophils into the parenchyma that induced by ischemia [41]. Hence, we guessed that TLR4 may be involved in the ischemic stroke affected by miR-140-5p, which was validated by means of RT-qPCR, Western blot, ow cytometry, and TTC staining, as well as TUNEL staining.…”
Section: Discussionmentioning
confidence: 78%
“…A generally accepted view is that the amount of collateral-dependent blood ow is one of the dominating determinants of infarct volume after LVO [26]. Therefore, rarefaction of the preexisting collateral circulation, results in more severe tissue injury and augmented neuronal necrosis following arterial occlusion; then, endogenous molecules are released from damaged cells amplifying in ammatory mediator expression and tissue damage by triggering and inducing the activation of Toll-like receptors (TLRs) [27], and some other damage-associated molecular patterns (DAMPs) [28]. Furthermore, collateral remodeling involves endothelial cell activation, leukocyte recruitment, matrix changes and cell proliferation; for patients with poor collateral circulation, the proin ammatory process involving angiogenesis will be more obvious [29].…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition of TLR2 signaling pathway regulates leukocytes and microglial infiltration and the subsequent neuronal death after mild AIS [78,87,104,105]. Inhibition of TLR4 could attenuate the inflammation and H-I damages through blockade of tissue-type plasminogen activator-induced hemorrhagic transformation [106] as well as enhancement of the ratio of alternative neutrophils [15]. It has been shown that TLR4-deficient mice have significantly less tolerance to H-I insults than wild-type mice, possibly via the lesser expression of TNFα, cyclooxygenase-2 (COX-2), and NF-κB [107].…”
Section: Tlr9mentioning
confidence: 99%
“…Accumulating evidence suggest that TLRs play a crucial role in the pathogenesis of AIS [15,16], ICH [17,18], and SAH [19]. TLRs activation following ischemic insults could be pathogenic or neuroprotective, depending on the context.…”
Section: Introductionmentioning
confidence: 99%